OPTIMIZATION OF CARBOPOL 940 AND OLEIC ACID IN DICLOFENAC SODIUM BASE GEL USING FACTORIAL DESIGN 22 METHOD - Rahmawati, Eka Diana; Bhagawan, Weka Sidha; Rizkiah, Fidia (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
The aim of the present study was to determine the effect of carbopol 940, oleic acid and interaction of both in the value of viscosity and release rate and to find optimum formula of diclofenac sodium base gel which can produced viscoisity between 20 dPa.s - 200 dPa.s and rate release 50Î¼g/cm2.menit1/2 - 150Î¼g/cm2.menit1/2 using factorial design 22. The level of carbopol 940 were 1,3% and 0,8% while the level of oleic acid were 5% and 20%. Analysis of the research used Design Expert 10 software.The results showed that carbopol 940 and oleic acid had significant effect in determining the viscosity response and the release rate. The addition of carbopol 940 and oleic acid l increased the viscosity response and the addition of carbopol 940 and oleic acidÂ decreased the release flux response. There were 100 optimum compositions of combination of carbopol 940 between 0.8% to 1,194% and oleic acid between 5% and 19.95% which can be used to obtain sodium diclofenac base gel preparation with viscosity responses between 76,042 dPa.s -199,570 dPa.s and flux release responses from 101,000 Î¼g/cm2.minute1/2 until 124,250 Î¼g/cm2.minute1/2.